THE EFFECTIVENESS OF THE KRPPA PROGRAM FOR GENDER MAINSTREAMING IN BABAT JERAWAT VILLAGE - Pitaloka, Yanesty Ayu; Astuti, Sri Juni Woro (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2025)
The Women and Child Friendly Village Programme (KRPPA) is a government initiative introduced by the Ministry of Women’s Empowerment and Child Protection to strengthen gender mainstreaming and child protection at the local level. This study aims to analyse the effectiveness of KRPPA in Babat Jerawat Urban Village, Surabaya. A qualitative descriptive method was employed, involving five key informants consisting of DP3APPKB staff, village officials, KSH cadres, community leaders, and female residents. Data were collected through in-depth interviews, observations, and documentation, and were analysed based on seven dimensions of programme effectiveness: clarity of objectives, resources, participation, coordination, programme quality, evaluation, and impact. The results indicate that KRPPA in Babat Jerawat is “fairly effective”. Activities such as family health posts, parenting classes, and premarital courses support the programme’s indicators, but implementation remains limited to health and social aspects. The main obstacles are the lack of continuous training, weak cross-agency coordination, and the absence of participatory evaluation. These findings suggest that the effectiveness of KRPPA at the local level requires further strengthening in terms of socialisation, cadre capacity building, and inter-agency synergy to achieve its objectives more optimally.